2018
DOI: 10.1111/desc.12643
|View full text |Cite
|
Sign up to set email alerts
|

Phonological processing during silent reading in teenagers who are deaf/hard of hearing: an eye movement investigation

Abstract: There has been considerable variability within the literature concerning the extent to which deaf/hard of hearing individuals are able to process phonological codes during reading. Two experiments are reported in which participants' eye movements were recorded as they read sentences containing correctly spelled words (e.g., church), pseudohomophones (e.g., cherch), and spelling controls (e.g., charch). We examined both foveal processing and parafoveal pre-processing of phonology for three participant groups-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 43 publications
1
22
1
Order By: Relevance
“…Based on a masked phonological priming paradigm, Gutierrez-Sigut et al (2018) reported that deaf individuals showed faster word identification times in the pseudo-homophone than in the control condition. Similar results were reported in a study using both behavioural and ERP measures (Gutierrez-Sigut et al, 2017) and in a study on English children by Blythe et al (2018). Transler and Reitsma (2005) found that pseudo-homophony effects were present but smaller in deaf individuals than in hearing controls.…”
Section: Introductionsupporting
confidence: 85%
“…Based on a masked phonological priming paradigm, Gutierrez-Sigut et al (2018) reported that deaf individuals showed faster word identification times in the pseudo-homophone than in the control condition. Similar results were reported in a study using both behavioural and ERP measures (Gutierrez-Sigut et al, 2017) and in a study on English children by Blythe et al (2018). Transler and Reitsma (2005) found that pseudo-homophony effects were present but smaller in deaf individuals than in hearing controls.…”
Section: Introductionsupporting
confidence: 85%
“…These studies show that when a word in a text is fixated, identities of letters and their corresponding phonemes are activated early during the fixation. Blythe et al [77] reported on two experiments in which participants' eye movements were recorded as they silently read sentences containing correctly spelled words (e.g., church), pseudohomophones (e.g., cherch), and spelling controls (e.g., charch). Three groups were tested: teenagers with permanent childhood hearing loss (PCHL), chronological age-matched controls, and reading age-matched controls.…”
Section: Phonological Processing In Word Recognitionmentioning
confidence: 99%
“…For each triplet, one sentence frame was used in Experiment 1 and the other sentence frame in Experiment 2 so that, in each experiment, each participant read 24 experimental sentences. Full details of the pre-screening, and the full list of stimuli have already been published [53]. Note that the pre-screening was conducted with 8-9 year old children, so as to be confident that the teenagers with a history of dyslexia who took part in the eye movement study would be able to read and understand the sentences despite their reading difficulties (these teenagers being recruited from Years 9-13, so possibly as young as 13 and with severe reading difficulties, depending on voluntary participation).…”
Section: Stimuli and Designmentioning
confidence: 99%
“…Some pseudohomophones and spelling controls, particularly in the orthographically dissimilar condition, bore little resemblance to the lexical entry with which they corresponded (e.g., honey, hunni, henma). For this reason, each sentence was written to be semantically constraining for the target word (at least 60% of 8-9 year old children in the pre-screening study predicted each target word from its surrounding sentence context [53]). It may be that these highly constraining sentences facilitated the readers' phonological recoding of the target words/nonwords.…”
Section: Plos Onementioning
confidence: 99%